2016
DOI: 10.1002/met.1581
|View full text |Cite
|
Sign up to set email alerts
|

Aviation turbulence encounters detected from aircraft observations: spatiotemporal characteristics and application to Korean Aviation Turbulence Guidance

Abstract: Using observational data from Korean Air Lines (KAL) Boeing (B) 737‐800, B777‐200 and B777‐300 flights from January to December 2012, the derived equivalent vertical gust velocity (DEVG) was calculated as a turbulence indicator. Based on 1 min flight segments using the calculated DEVG, the highest frequency of moderate‐or‐greater (MOG) turbulence occurred in the Northern Hemisphere winter, whereas the lowest frequency occurred in the Northern Hemisphere summer. Spatially, the KAL turbulence encounters (KAL‐DEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…This is much smaller than the grid spacing of the current (and near-future version of) global NWP models. However, because the energy of the large-scale disturbances cascades down to smaller scales (e.g., Cho and Lindborg 2001), aircraft-scale turbulence can be logically predicted using NWP model-based turbulence diagnostics formulated based on the aforementioned turbulence generation mechanisms (e.g., Gill 2014;Kim et al 2011Kim et al , 2015Kim and Chun 2016;Sharman et al 2006;Sharman and Pearson 2017).…”
Section: Requirements Resolutionmentioning
confidence: 99%
“…This is much smaller than the grid spacing of the current (and near-future version of) global NWP models. However, because the energy of the large-scale disturbances cascades down to smaller scales (e.g., Cho and Lindborg 2001), aircraft-scale turbulence can be logically predicted using NWP model-based turbulence diagnostics formulated based on the aforementioned turbulence generation mechanisms (e.g., Gill 2014;Kim et al 2011Kim et al , 2015Kim and Chun 2016;Sharman et al 2006;Sharman and Pearson 2017).…”
Section: Requirements Resolutionmentioning
confidence: 99%
“…Any two independent constraints on the cumulative distribution function of the log-normal distribution will uniquely define the values of these two parameters. Here, we require that the probability of light-or-greater turbulence (with a cube-rooted eddy dissipation rate greater than 0.1 m 2/3 s −1 ) is 3.0% (Watkins and Browning, 1973;Kim and Chun, 2016) and that the probability of moderate-orgreater turbulence (with a cube-rooted eddy dissipation rate greater than 0.3 m 2/3 s −1 ) is 0.4% (Sharman et al, 2006;Kim and Chun, 2016). This definition of moderate-or-greater turbulence is slightly different from the one used by Williams and Joshi (2013).…”
Section: 2)mentioning
confidence: 99%
“…They found that the intermittent gust, which created a severe crosswind over the runaways, was associated with undulations in a train of lee waves in the mid‐troposphere in a stable layer above the airport, creating descending strong winds towards the surface. Kim and Chun () used observational data recorded by some flights of Korean Air Lines to obtain the derived equivalent vertical gust velocity as a turbulence indicator. They found an average of one turbulence per flight and per 10 h of navigation, mainly following the jet stream.…”
Section: Introductionmentioning
confidence: 99%